Rational Inattention in Social Topics - Kunc, Benjamín; Cingl, Lubomír, 1984-; Špecián, Petr; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2020)
This thesis studies the implications of economic and behavioral theories about inattention on the political polarization. Also, potential approaches to reducing polarization and its causing effects are studied. In the Introduction part, the importance of polarization for economic fields is discussed. The second part surveys some of the knowledge from psychology and economics of attention in order to choose a plausible economic model of inattention. In the last part, an experiment is conducted to test its implications. Economic and psychological literature assumes the existence of the effect of prior beliefs of individuals and monetary motivation on the attention to information. In this thesis, there has been found only effect of financial motivation on the willingness to spend time by acquiring information and then by answering. No effect of financial incentives or prior beliefs on the allocation of attention has been found.
Vedoucí práce: Lubomír Cingl
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses